2020
DOI: 10.5194/bg-17-187-2020
|View full text |Cite
|
Sign up to set email alerts
|

Flux variability of phyto- and zooplankton communities in the Mauritanian coastal upwelling between 2003 and 2008

Abstract: Abstract. Continuous multiyear records of sediment-trap-gained microorganism fluxes are scarce. Such studies are important to identify and to understand the main forcings behind seasonal and multiannual evolution of microorganism flux dynamics. Here, we assess the long-term flux variations and population dynamics of diatoms, coccolithophores, calcareous and organic dinoflagellate cysts, foraminifera and pteropods in the eastern boundary upwelling ecosystem of the Canary Current. A multiannual, continuous sedim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(65 citation statements)
references
References 112 publications
(203 reference statements)
8
55
0
2
Order By: Relevance
“…For this study, a total of 282 sediment trap samples were processed. Each sample was chemically treated with potassium permanganate, hydrogen peroxide (33 %), and concentrated hydrochloric acid (32 %) following previously used methodology (Romero and Fischer, 2017;Romero et al, 1999aRomero et al, , b, 2002Romero et al, , 2009aRomero et al, , b, 2020. Qualitative and quantitative analyses of the diatom community were carried out on permanent slides of acid-cleaned material (Mountex ® mounting medium) at ×1000 magnification by using a Zeiss ® Axioscope with phase-contrast illumination (MARUM, University of Bremen).…”
Section: Assessment Of Diatom Fluxes and Species Identificationmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, a total of 282 sediment trap samples were processed. Each sample was chemically treated with potassium permanganate, hydrogen peroxide (33 %), and concentrated hydrochloric acid (32 %) following previously used methodology (Romero and Fischer, 2017;Romero et al, 1999aRomero et al, , b, 2002Romero et al, , 2009aRomero et al, , b, 2020. Qualitative and quantitative analyses of the diatom community were carried out on permanent slides of acid-cleaned material (Mountex ® mounting medium) at ×1000 magnification by using a Zeiss ® Axioscope with phase-contrast illumination (MARUM, University of Bremen).…”
Section: Assessment Of Diatom Fluxes and Species Identificationmentioning
confidence: 99%
“…We discuss the new results in view of the high frequency of climate indices, which are proxies for atmospheric and hydrographic dynamics along the CC EBUE, and low-frequency climate variability in the North Atlantic, and we compare our new data set at the site CBmeso with previous diatom (Romero and Fischer, 2017;Lange et al, 1998;Romero et al, 1999aRomero et al, , b, 2002Romero et al, , 2020 and bulk flux results off Mauritania (Helmke et al, 2005;Fischer et al, 2016Fischer et al, , 2019. We also discuss our new results with recent results from the nearby coastal site CBeu (Cape Blanc eutrophic) (Romero and Fischer, 2017;Romero et al, 2020). We used deep-moored (> 700 m water depth), largeaperture time-series sediment traps of the Kiel and Honjo types with 20 cups and 0.5 m 2 openings, equipped with a honeycomb baffle (Kremling et al, 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The year 2005 was discussed by Fischer et al (2016Fischer et al ( , 2019 as an exceptional year with high fluxes despite a low NAO. Romero and Fischer (2017) and Romero et al (2020) found a change in diatom fluxes and composition at the coastal Cape Blanc site (CB eu) starting in 2005/2006. Unusually high particle fluxes in 2005 in the bathypelagic were also observed far offshore at site Kiel 276 (ca.…”
Section: Nao Controls and An Increased Emphasis In Spring-time Fluxesmentioning
confidence: 99%